Phamacology of fluticasone furoate and vilanterol trifenatate combination therapy for asthma. (2nd October 2016) - Chang, Vicky; Gray, Emma L.; Thomas, Paul S.
ABSTRACT: Introduction : Fluticasone furoate (FF) is a novel inhaled corticosteroid (ICS). Vilanterol trifenate (VI) is a new inhaled, selective, long – acting β2 adrenergic agonist (LABA). It is now also marketed as a novel once daily combined ICS/LABA indicated for treatment of moderate and severe asthma. Areas covered : FF has a highly specific, fast association and slow dissociation from the glucocorticoid receptor, with a 24 hr duration of action. This, combined with a slow transport out of respiratory cells, creates a long tissue retention period. Vilanterol trifenate (VI) is a new inhaled, selective, long – acting β2 adrenergic agonist, also with a rapid onset of action with a maximal effect within 6 mins and prolonged lung retention with effects on lung function over 24 hours. Expert commentary : Multiple Phase I–III efficacy studies performed on FF and VI have shown an improvement in spirometry as well as symptom control in asthma. The development of once daily ICS/LABA combinations may potentially improve adherence to asthma therapy, but this has yet to be demonstrated.